The Role and Challenges of the Constitutional Court as a Positive Legislature amid Indonesia’s Democratic Regression: Peranan dan Problematika Mahkamah Konstitusi sebagai Positive Legislature di Tengah Regresi Demokrasi Indonesia - Muhammad, Raihan (Universitas Islam Indonesia, 2025)
Indonesia is currently experiencing a democratic regression, marked by increasing political corruption, restrictions on press freedom, and the weakening of independent institutions, including the Constitutional Court. As an institution tasked with safeguarding the Constitution, the Court is ideally expected to function as a negative legislature—annulling unconstitutional legal norms without creating new ones. However, in recent years, the Court has increasingly acted as a positive legislature by formulating new norms to fill legal gaps. While this move aims to protect citizens' constitutional rights, the absence of clear regulations regarding the scope of the Court’s authority as a positive legislature has led to legal uncertainty and opened the door to potential abuse of power. This study uses normative legal research with a doctrinal approach to analyze the impact of democratic regression on the credibility and effectiveness of the Constitutional Court in fulfilling its role as a positive legislature. The findings indicate that without clear regulatory boundaries, the Court's role risks reinforcing elite political hegemony, disrupting the separation of powers, and undermining public trust in its independence. Therefore, it is recommended that the government and the House of Representatives establish explicit regulations on the Court's authority in exercising its positive legislative function. Additionally, a stricter oversight mechanism is necessary to ensure that the Constitutional Court remains independent and consistent in upholding the rule of law and constitutional democracy in Indonesia.